Waiting it out: consultation delays prolong in-patient length of stay. Issue 1119 (23rd January 2019) - Rahman, Arifeen Sylvanna; Shi, Siyu; Meza, Pamela Katherine; Jia, Justin Lee; Svec, David; Shieh, Lisa
Abstract: Background: Decreasing delays for hospitalised patients results in improved hospital efficiency, increased quality of care and decreased healthcare expenditures. Delays in subspecialty consultations and procedures can cause increased length of stay due to reasons outside of necessary medical care. Objective: To quantify, describe and record reasons for delays in consultations and procedures for patients on the general medicine wards. Methodology: We conducted weekly audits of all admitted patients on five Internal Medicine teams over 8 weeks. A survey was reviewed with attending physicians and residents on five internal medicine teams to identify patients with a delay due to consultation or procedure, quantify length of delay and record reason for delay. Results: During the study period, 316 patients were reviewed and 48 were identified as experiencing a total of 53 delays due to consultations or procedures. The average delay was 1.8 days for a combined total of 83 days. Top reasons for delays included scheduling, late response to page and a busy service. The frequency in length of consult delays vary among different specialties. The highest frequency of delays was clustered in procedure-heavy specialties. Conclusion: This report highlights the importance of reviewing system barriers that lead to delayed service in hospitals. Addressing these delays could lead to reductions in length of stay for inpatients.